Gambaran Pemahaman Masyarakat Dalam Pemanfaatan Tanaman Obat Keluarga di Desa Pacar Kecamatan Tirto Kabupaten Pekalongan - Heni, Heni Setyorini; Nur Ermawati; Ali Mansyur (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Family medicinal plants are plants cultivated at home that have medicinal properties. That use of TOGA is generally for general treatment such as coughs and stomachaches. Planting medicinal plants in the yard, in addition to being used for medicine, can also be used well as a decoration for the yard. This study aims to determine the description of understanding in the use of family medicinal plants in Pacar Village, Tirto District, Pekalongan Regency. The method used to collect data in this study was purposive sampling, and the questionnaire used in this study consisted of several semi-open questions, namely multiple choice and essay. The results of this study showed that all respondents had undergone treatment using TOGA, as many as 51% of respondents used TOGA to treat flu/cough, the treatment period 1 week or even more than 1 week with an effectiviness level reaching 85%. The majority of respondents who used ginger were 51%, lemongrass 18%, and turmeric 14%. Information about TOGA was partly obtained from social media 41%, and family inheritance from generation to generation as much as 39%. The most commonly used part of TOGA is the rhizome 75%, and the safety of use is safe is used properly. Most respondents get TOGA by buying it and the rules for using it are 2-3 times a day, by processing it by boiling, slicling, and grating. Keywords : Pacar Village, Benefits of TOGA, Purposive sampling